Vasculogenic mimicry and matrix metalloproteinase MMP-9 expression in women with ovarian tumors - Czekierdowski, Artur; Czekierdowska, Sylwia; Daniłoś, Jarosław; Rogala, Ewelina; Nowicka, Aldona (Menopause Review/Przegląd Menopauzalny, 2012)
Background: Fast growing malignant tumors may use pathways alternative to endothelial angiogenesis vascularization pathways including vasculogenic mimicry (VM). Matrix metalloproteinases (MMPs) are important components of molecular switch to VM, but their possible contribution to VM formation in ovarian malignant tumors is not known. Aim of the study : Our goal was to examine the MMP-9 and VM expression in malignant and benign ovarian tumors. Material and methods : The study group comprised 67 women of whom 41 were postmenopausal. Mean age was 53.6 ±10.45 yrs (median 54 yrs, range: 23-86 yrs). Immunohistochemical MMP-9 expression with periodic acid-Schiff (PAS) staining for non-endothelial cell-lined blood vessels that were formed by tumor cells indicating vasculogenic mimicry were analyzed in all masses. There were 62 malignant tumors in the studied group. FIGO clinical stage and tumor histological grade (G1-G3) were compared with VM and MMP-9 expression assessed in serial histological preparations. Results : MMP-9 expression was found in 52 tumors (77.6%) and its strength (weak-medium-strong) was significantly correlated with the tumor histological type. Significant differences were found between benign tumors that had no or only a weak MMP-9 expression and malignant masses in which a medium or strong MMP-9 expression was found more frequently (26/45 cases of FIGO st. III tumors, Ch 2 2=13.1; p = 0.04). A high MMP-9 expression was found in 20% of primary ovarian cancer cases. No significant differences were found when malignant tumor histological grade or menopausal status of studied women were compared with MMP-9 expression (Chi 2 = 6.4; p = 0.37). PAS-positive structures indicating presence of VM were found in 30 (44.7%) ovarian cancers. MMP-9 was more frequently found in tumors with VM (Chi 2 = 15.8; p = 0.001). In 30 masses with PAS-positive structures, MMP-9 expression was more frequently high (11 cases) or medium (6 cases). All 37 masses without VM detected with PAS-positive reaction had a weak MMP-9 expression. Conclusions : Matrix metalloproteinase-9 appears to play an important role in the development of vasculogenic-like networks and matrix remodeling in a significant proportion of malignant ovarian tumors. Studies on the potential role of molecular factors controlling ovarian cancer vascularization pathways may be used in the future to develop new tumor angiogenesis blocking agents.